EVALUATION OF ABSENCE OF CLINICAL PALLOR IN RECRUITS - Alam, Maqbool; Akram, Saeed (Pakistan Armed Forces Medical Journal, 2011)
Objective: Clinical findings such as pallor of the conjunctivae, nail beds, lips, oral mucosa and palmar creases have been used by physicians in the diagnosis of anaemia. This study was carried out to determine the value of absence of clinical pallor in ruling out anaemia in recruits by measuring blood haemoglobin concentration as a true standard. Study Design: A cross-sectional descriptive study. Place and duration of Study: Pathology department of Combined Military Hospital Sargodha from Jan 2009 to Jun 2009. Subjects and Methods: Young adults selected for recruitment in army after medical examination by general duty medical officers were included in the study. Haemoglobin estimation was done on Sysmex KX-21 semi automated haematology analyzer. Results: Out of total 1760 individuals who were not having conjunctival pallor as per assessment of the doctors, 109 (6.19%) were found anaemic (haemoglobin